2018
DOI: 10.5152/tjg.2018.18032
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation rates in patients using biological agents, with resolved HBV infection or isolated anti-HBc IgG positivity

Abstract: Drugs that block TNF-α and ustekunimab cause an increase in viral replication. In literature, the HBV reactivation rate was approximately 1% in HBsAg-negative, anti-HBC IgG-positive cases, whereas it was found to be as high as 17.2% in our study. Patients receiving the immunomodulator therapy should be evaluated for HBV serology before treatment and carefully monitored for HBV reactivation during and after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Of those remaining 27 articles which met inclusion criteria, a detailed search in their reference lists yielded 3 further studies which met the study's criteria for inclusion. In total, 29 articles 17–45 were included in this meta‐analysis (Figure 1). There was no data for vedolizumab and HBV reactivation apart from a single study, 46 and this was deemed to be not sufficient to be included in the meta‐analysis though it was included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those remaining 27 articles which met inclusion criteria, a detailed search in their reference lists yielded 3 further studies which met the study's criteria for inclusion. In total, 29 articles 17–45 were included in this meta‐analysis (Figure 1). There was no data for vedolizumab and HBV reactivation apart from a single study, 46 and this was deemed to be not sufficient to be included in the meta‐analysis though it was included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…All of the patients received ustekinumab for psoriasis, with the exception of one study with mixed indications, yet psoriasis was the predominant group. 21 No vedolizumab-specific demographic data could be obtained from the single study 46 as the data were combined for patients with and without hepatitis B virus.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…In another study involving 7 patients with resolved HBV on ustekinuamb, 1 patient (14.3%) developed HBVr. This patient was not on antiviral prophylaxis and started entecavir for treatment of HBVr[ 5 ]. These data suggest that there is a certain risk of HBVr in patients with resolved HBV even without detectable HBV-DNA at baseline after starting ustekinumab, suggesting that these patients might need antiviral prophylaxis as is the AGA guidelines preferred option.…”
Section: Il-12/23 Inhibitorsmentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-α is a key cytokine not only in the pathogenesis of autoimmune diseases but also in the host immune reactions against HBV infection. TNF-α is synthesized by macrophages and T cells and induce the production of a variety of inflammatory cytokines, suppressing viral replication[ 5 ]. TNF-α is also necessary for the proliferation of HBV-specific Tc cells that are essential for suppression of HBV replication[ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clarke et al [ 46 ] investigated the prevalence of HBVr in a single-center retrospective cohort analysis of 120 HBsAg-negative/anti-HBc-positive subjects (anti-TNF treatment in 19% of the cases), and found a low rate of HBV reactivation (0.8%). Solay et al [ 47 ] assessed 29 cases of patients with resolved HBV infection who received biological treatment: HBVr was observed in five patients (17.2). Pauly et al reported that not one of the 178 HBsAg-negative/anti-HBc-positive subjects treated with TNF antagonists had documented HBVr [ 22 ].…”
Section: Strategies For the Prevention And Treatment Of Hbv Reactivationmentioning
confidence: 99%